Renal allograft outcomes following early corticosteroid withdrawal in Hispanic transplant recipients. (6th September 2013) - Afaneh, Cheguevara; Cheng, Elaine; Aull, Meredith J.; Watkins, Anthony C.; Kim, Jim; Leeser, David B.; Kapur, Sandip
Abstract Background Renal transplant outcomes in Hispanics have been conflicting regarding acute rejection (AR) and allograft survival. Additionally, the feasibility of early corticosteroid withdrawal (ECW) regimens among Hispanics has not been adequately addressed. The purpose of this study is to report outcomes following ECW among Hispanic renal transplant recipients. Methods We retrospectively reviewed 498 consecutive renal transplants performed at our institution between July 2005 and October 2007, including 73 Hispanic and 146 white recipients who had ECW (median follow‐up 49 months). Demographics, transplant data, and outcomes of Hispanic and white recipients (WR) were analyzed. Results Hispanics had a higher incidence of diabetes mellitus and hypertension (p = 0.007), a higher proportion of blood type O (p = 0.006), and a higher serum panel reactive antibody at the time of transplantation (p = 0.02) compared with WR. Additionally, Hispanics were on dialysis longer than WR prior to transplantation (p = 0.03). Nevertheless, the incidence of AR, patient, and graft survival rates was similar (p > 0.05) between Hispanics and WR. Ethnicity was not an independent predictor of inferior patient and graft outcomes in multivariate analyses. Conclusion Our single‐center experience indicates that ECW can be performed in Hispanic renal transplant recipients, with patient and allograft outcomes comparable with those observed in WR.